2021
DOI: 10.1186/s12913-021-06411-6
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19’s impact on faculty and staff at a School of Medicine in the US: what is the blueprint for the future?

Abstract: Background The Coronavirus Disease 2019 (COVID-19) caused unprecedented challenges within medical centers, revealing inequities embedded in the medical community and exposing fragile social support systems. While faculty and staff faced extraordinary demands in workplace duties, personal responsibilities also increased. The goal of this study was to understand the impact of the COVID-19 pandemic on personal and professional activities of faculty and staff in order to illuminate current challeng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
1
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 48 publications
(54 reference statements)
0
21
1
1
Order By: Relevance
“…Many predict it will raise existing barriers to success, leading women to flounder in early career positions or leave the workforce [ 28–31 ]. A few early studies have shown that the publication gender gap has persisted throughout the COVID-19 pandemic [ 32 ], and has resulted in fewer publications by women and fewer women scientific experts and leaders being quoted in the media on the pandemic itself [ 33 , 34 ]. These publication and media biases have the potential to have long-lasting effects on gender disparities in academic medicine.…”
Section: Introductionmentioning
confidence: 99%
“…Many predict it will raise existing barriers to success, leading women to flounder in early career positions or leave the workforce [ 28–31 ]. A few early studies have shown that the publication gender gap has persisted throughout the COVID-19 pandemic [ 32 ], and has resulted in fewer publications by women and fewer women scientific experts and leaders being quoted in the media on the pandemic itself [ 33 , 34 ]. These publication and media biases have the potential to have long-lasting effects on gender disparities in academic medicine.…”
Section: Introductionmentioning
confidence: 99%
“…Similar concerns have been raised in other studies, with employees requesting a continuation of flexible pandemic policies and using the momentum of change to improve other inequitable policies. 3,5,12 University participants have reported increased physical exhaustion and anxiety or fear about both the personal health and interpersonal relationship consequences of a positive test. 3,4,21 One study found that university students who tested positive for COVID-19 were more likely to experience food insecurity or mental health disorders such as anxiety and depression.…”
Section: Discussionmentioning
confidence: 99%
“…Data were analyzed using an inductive thematic approach as in prior work. 4,5,12,18,19 FGDs and interviews were recorded via Zoom; voice-to-text transcriptions were then cleaned and de-identified by study staff. Analysis was performed using Dedoose software (Version 9.0.17, 2021, Los Angeles, CA).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations